2015
DOI: 10.1002/smi.2640
|View full text |Cite
|
Sign up to set email alerts
|

Skin Barrier Recovery is not Associated with Self-Perceived Stress

Abstract: The primary aim of the current study was to examine the association between self-perceived stress and skin-barrier recovery. From an initial sample of 410 students, 19 high-stress and 12 low-stress Hispanic women completed a behavioural survey and were assessed for recovery of skin barrier following a tape-stripping procedure. No association was found between self-perceived stress and skin barrier recovery at either the 30-min or 3.15-h recovery period. Supplemental analysis showed a positive correlation betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Despite studies reporting correlations between stress or unhappiness and epidermal barrier function changes, Benham argues that skin barrier recovery is not associated with the Perceived Stress Scale . In a case–control study utilizing a behavioural survey, self‐perceived stress did not significantly correlate with skin barrier recovery among high‐stress and low‐stress women .…”
Section: Social and Marital Stressmentioning
confidence: 92%
“…Despite studies reporting correlations between stress or unhappiness and epidermal barrier function changes, Benham argues that skin barrier recovery is not associated with the Perceived Stress Scale . In a case–control study utilizing a behavioural survey, self‐perceived stress did not significantly correlate with skin barrier recovery among high‐stress and low‐stress women .…”
Section: Social and Marital Stressmentioning
confidence: 92%
“…Fukuda et al ( 2015 ) found an association between psychological stress, measured as salivary α-amylase and chromogranin A, and impaired SC and recovery after tape striping. The result could not be confirmed in a similar study by Benham ( 2016 ) who used self-reported stress (PSS) to assess stress. One possible explanation for the different results could be a difference in severity of created skin damage between the studies.…”
Section: Discussionmentioning
confidence: 76%
“…This study demonstrated that women who were classified as good sleepers according to the Pittsburgh Sleep Quality Index questionnaire presented fewer signs of intrinsic skin ageing, a greater rate of recovery from erythema after solar-simulating radiation and a 30% greater barrier recovery in comparison to those considered as poor sleepers (OyetakinWhite et al, 2015). Moreover, another study found that SPS was not associated with skin barrier recovery, so that no significant differences on skin barrier recovery were found between the low and high SPS groups (Benham, 2015). However, when evaluating the self-reported sleep duration they found a positive correlation with skin barrier recovery.…”
Section: To the Editormentioning
confidence: 92%
“…However, when evaluating the self-reported sleep duration they found a positive correlation with skin barrier recovery. This result demonstrated that sleep debt could slow skin barrier recovery and better explain their results (Benham, 2015).…”
Section: To the Editormentioning
confidence: 94%